ANALISIS PROSES PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) MATEMATIKA DENGAN PENDEKATAN ILMIAH (SCIENTIFIC APPROACH ) DI SMA NEGERI 1 JOGOROGO KELAS X TAHUN PELAJARAN 2013 / 2014 KABUPATEN NGAWI - Arum Dwi Rahmawati Dwi Rahmawati; Riyadi Riyadi; Sri Subanti (Universitas Sebelas Maret, 2014)
Abstract: The purpose of this research was to describe the planning, implementation process of learning undertaken by teachers of mathematics and constraints experienced during the process of mathematical problem-based learning with a scientific approach in class X SMAN 1 Jogorogo. This research was a qualitative study. These subject are taken using purposive sampling. The subjects of this study were the teacher math in class X. Data collection techniques in this study were documentation, interviews and observations. Techniques to validate that the data source triangulation and triangulation time. The data analysis technique used was the concept of Miles and Huberman consists of data reduction, data display, and conclusion. The results showed that the planning process of mathematical problem-based learning with a scientific approach was not maximal yet, seen in the preparation of lesson plans which teachers only see examples of other schools and only see a reference to the syllabus. Implementation of the learning process is done the math teacher in class X SMAN 1 Jogorogo was not maximal yet. Visible in the indicator 5M on core activities are observing, asking, gather information, and communicate their associates have not done all. In observing the activities of students had no difficulty, however, go into the next phase indicator and students are still difficulties in doing so. In the event of problem making students ask questions, lack of motivation and imagination. Collect information on the activities of students also have difficulty in learning resources are used only for math books grade students associate X. At this stage also looks still difficulty in processing information, although sometimes the teacher has given direction that the students tried to process the information that has been obtained. At that last stage quite well in communicating the results, good enough student responses revealed the results even though the teacher had to call one of the students without first. Overcoming the problems found in the process of mathematical problem-based learning with a scientific approach to teacher always gives motivation at any stage of learning and trying to develop a problem-based learning with a scientific approach. Keywords: PBL, Scientific Approach